2013
DOI: 10.1016/j.jams.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity of Methanol Extract of Melastoma malabathricum Leaf in Rats

Abstract: The present study aimed to determine the hepatoprotective activity of a methanol extract of Melastoma malabathricum leaves (MEMM) using two established rat models. Ten groups of rats (n=6) were given a once-daily administration of 10% dimethyl sulfoxide (negative control), 200 mg/kg silymarin (positive control), or MEMM (50, 250, or 500 mg/kg) for 7 days followed by induction of hepatotoxicity either using paracetamol or carbon tetrachloride. Blood samples and livers were collected for biochemical and microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…[20] showed that the aqueous extract L. nepetifolia, given as chronic post-treatment, protected against CCl 4 -induced hepatic damage in rats in a similar manner. Additionally, several studies have shown that the methanol and aqueous extracts of some medicinal plants protect against APAPinduced hepatotoxicity by abrogating the drug-induced increase in liver enzymes and maintaining normal liver morphology [21][22][23][24]. Several studies have identified antioxidant phytochemicals, such as polyphenols and flavonoids, which were suggested to be responsible for the medicinal plants' protective properties against APAP-induced hepatic injury [25][26][27][28].…”
Section: Pre-treatment and Post-treatment Effects Of Extracts On Hepamentioning
confidence: 99%
“…[20] showed that the aqueous extract L. nepetifolia, given as chronic post-treatment, protected against CCl 4 -induced hepatic damage in rats in a similar manner. Additionally, several studies have shown that the methanol and aqueous extracts of some medicinal plants protect against APAPinduced hepatotoxicity by abrogating the drug-induced increase in liver enzymes and maintaining normal liver morphology [21][22][23][24]. Several studies have identified antioxidant phytochemicals, such as polyphenols and flavonoids, which were suggested to be responsible for the medicinal plants' protective properties against APAP-induced hepatic injury [25][26][27][28].…”
Section: Pre-treatment and Post-treatment Effects Of Extracts On Hepamentioning
confidence: 99%
“…Rats with carbon tetrachloride (CCl4)-induced liver injury were used to assess the hepatoprotective and antioxidant effect of MIE in vivo. The level or activity of alkaline phosphatase (ALP), glutamate pyruvate transaminase (ALT), aspartate aminotransferase (AST), and total bilirubin (TB) in the blood serum and thiobarbituric acid reactive substances (TBARS), superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) in the liver and kidney of the rats were assayed using standard procedures 48 . 40.…”
Section: Meconopsis Integrifoliamentioning
confidence: 99%
“…Melastoma malabathricum possesses a myriad of chemicals exhibiting antibacterial (Alwash, 2013;Choudhury et al, 2011;Omar et al, 2012), anti-inflammatory, antioxidant (Susanti et al, 2008), antidiarrheal (Sunilson et al, 2009, antiulcer (Balamurugan et al, 2013), antidiabetic (Balamurugan et al, 2014), and hepatoprotective properties (Kamisan et al, 2013). Biological activities of M. malabathricum are closely mediated via a wide range of bioactive chemical constituents such as flavonoids, flavonoid glycosides, terpenoids, steroids, anthocyanins, and tannins (Joffry et al, 2012;Susanti et al, 2008;Wong et al, 2012;Yoshida et al, 1992).…”
Section: Introductionmentioning
confidence: 99%